POLISH EXPERIENCE IN THE DEVELOPMENT OF INTERNATIONAL MUSIC FESTIVALS (ON THE EXAMPLE OF THE INTERNATIONAL FESTIVAL OF BRASS BANDS AND BIG BANDS IN LOBEZ) - Cherusheva, Galyna; Barvinok, Iryna (European Science, 2023)
the article deals with music festival as a form of cultural interaction and analyzes the history of formation and practice of implementation of the international festival of brass bands and big bands, held annually in Lobez (Poland)